2000
DOI: 10.1016/s0960-9822(00)00444-9
|View full text |Cite
|
Sign up to set email alerts
|

Proviral insertions in the zebrafish hagoromo gene, encoding an F-box/WD40-repeat protein, cause stripe pattern anomalies

Abstract: The zebrafish, Danio rerio, has three types of pigment cells (melanophores, xanthophores and iridophores) and, in adult fish, these cells are organized into a stripe pattern. The mechanisms underlying formation of the stripe pattern are largely unknown. We report here the identification and characterization of a novel dominant zebrafish mutation, hagoromo (hag), which was generated by insertional mutagenesis using a pseudotyped retrovirus. The hag mutation caused disorganized stripe patterns. Two hag mutant al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 22 publications
1
58
0
Order By: Relevance
“…The e9terminal types included e9terminal-fl that contained nine exons and resembled the zebrafish cDNA (17) [ (1) Because a hag cDNA probe containing exons 2 and 3 hybridized to a single band on a genomic Southern blot (see Fig. 5, which is published as supporting information on the PNAS web site, www.pnas.org), we concluded that these various subtypes of mRNA were generated from a single hag gene by alternative splicing by intron retention and͞or exon skipping.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The e9terminal types included e9terminal-fl that contained nine exons and resembled the zebrafish cDNA (17) [ (1) Because a hag cDNA probe containing exons 2 and 3 hybridized to a single band on a genomic Southern blot (see Fig. 5, which is published as supporting information on the PNAS web site, www.pnas.org), we concluded that these various subtypes of mRNA were generated from a single hag gene by alternative splicing by intron retention and͞or exon skipping.…”
Section: Resultsmentioning
confidence: 99%
“…The antisense probe can potentially hybridize to all hag transcripts. In zebrafish, expression of the hag gene is ubiquitous during all stages of development and in almost all adult tissues (17). The expression of hag was detected in a skin sample from a whole-body skin preparation from Haplochromis sp.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations